Required and possessed Nigerian University graduates employability quality: Perception of Gombe State employers of labour - Yauta, Ahmed Sani; Adepoju, Oluwasanumi A; Sulai, Mary E.; Tsakuwa, Mustapha Bala; Bala, Sani Fatima (African Journal of Behavioural and Scale Development Research, 2021)
This study investigated the perception of Gombe State employers of labour on the required employability quality of Nigerian university graduates' employability. The study adopted the survey design in which two research questions were set. The research was carried out in Gombe State, Nigeria. The multi-stage stratified random sampling technique was used to select the participating organizations and individual respondents. A total of 336 organisations constituted the study sample. A scale titled “Nigerian University Graduate Employability Quality Scale (NUGEQS)” was developed byx the researchers for data collection. The scale has two versions (Employers' Expectations and Employers' Rating). Data were analyzed using descriptive statistics of simple frequency counts and percentages and inferential statistics of chi-square.The findings revealed a mismatch between the employability skills expected by Gombe State employers of labour and the possessed skills by Nigerian university graduates. The paper recommended that curriculum planners and tertiary institutions should respond to the challenge of differences in the expected and actual qualities of Nigerian university graduates.